2022
DOI: 10.1186/s12870-022-03912-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanopriming-mediated memory imprints reduce salt toxicity in wheat seedlings by modulating physiobiochemical attributes

Abstract: Background Around the globe, salinity is one of the serious environmental stresses which negatively affect rapid seed germination, uniform seedling establishment and plant developments restricting sustainable agricultural productivity. In recent years, the concepts of sustainable agriculture and cleaner production strategy have emphasized the introduction of greener agrochemicals using biocompatible and natural sources to maximize crop yield with minimum ecotoxicological effects. Over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Diaspore dormancy/germination and persistence/depletion of A. centralasiatica diaspores in the soil seedbank were influenced by the seasonal fluctuation of climatic conditions, which differed among the three diaspore types, soil salinity and burial depth. Burial at 5 cm, high salinity and non-salinity inhibited germination of non-dormant seeds of diaspore types B and C, while high-saline stress and shallow soil burial depth delayed depletion of diaspore A, B and C. Unlike most studies on halophytes in which optimum germination occurred in non-saline condition [ 29 35 ], diaspores of A. centralasiatica germinated better in low soil salinity than in non-saline soil.…”
Section: Discussionmentioning
confidence: 55%
“…Diaspore dormancy/germination and persistence/depletion of A. centralasiatica diaspores in the soil seedbank were influenced by the seasonal fluctuation of climatic conditions, which differed among the three diaspore types, soil salinity and burial depth. Burial at 5 cm, high salinity and non-salinity inhibited germination of non-dormant seeds of diaspore types B and C, while high-saline stress and shallow soil burial depth delayed depletion of diaspore A, B and C. Unlike most studies on halophytes in which optimum germination occurred in non-saline condition [ 29 35 ], diaspores of A. centralasiatica germinated better in low soil salinity than in non-saline soil.…”
Section: Discussionmentioning
confidence: 55%
“…This in turn alarms the cells of cell wall degradation, e.g., by pathogens [ 49 ], the activation of signal transduction pathways, and the initiation of a cascade of plant biochemical defence mechanisms associated with e.g., the accumulation of secondary metabolites. Moreover, chitosan can interfere positively with complex cellular networks, including cellular signalling, redox homeostasis, and transcription processes, thereby modifying plant metabolic activities [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samea-Andabjadid et al (2018) reported that cytokinin and salicylic acid application to faba bean plant under salt stress in greenhouse conditions increased lipid peroxidation under stress conditions, but lipid peroxidation decreased with the effect of foliar application and cytokinin and salicylic acid application. Farooq et al (2022) It also reduced MDA contents (65-75%) and regulated ROS production resulting in improved membrane stability.…”
Section: Lipid Peroxidation (Mda)mentioning
confidence: 98%
“…Golkar et al (2021) reported that the phenolic content increased under stress conditions. Farooq et al (2022) reported that in nanopriming, hydropriming and control applications of wheat seeds, TPC decreased as the priming doses increased. He et al (2022) Mesembryanthemum crystallinum L. primed with sea water under salt stress.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%